2020
DOI: 10.1001/jamadermatol.2019.3508
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Topical Brimonidine on Alcohol-Induced Flushing in Asian Individuals

Abstract: IMPORTANCE Alcohol flushing syndrome (AFS, also known as Asian glow and Asian flush) affects 20% to 47% of East Asians and causes significant psychosocial distress. There are no approved treatments for this condition.OBJECTIVE To determine whether brimonidine gel, 0.33%, decreases facial erythema in patients with AFS after consumption of alcohol. DESIGN, SETTING, AND PARTICIPANTSIn this randomized clinical trial, 20 healthy volunteers of East Asian descent with a self-reported history of AFS were recruited bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Brimonidine also has additional mast cell-mediated anti-inflammatory properties and acts as a barrier [91,92]. In addition, a study showed that brimonidine was beneficial against alcohol-induced flushing and provided satisfaction in rosacea patients [93]. Both topical drugs could be used with topical, systemic, or instrumental therapies for rosacea.…”
Section: Topical Treatment For Erythematotelangiectatic Rosaceamentioning
confidence: 99%
“…Brimonidine also has additional mast cell-mediated anti-inflammatory properties and acts as a barrier [91,92]. In addition, a study showed that brimonidine was beneficial against alcohol-induced flushing and provided satisfaction in rosacea patients [93]. Both topical drugs could be used with topical, systemic, or instrumental therapies for rosacea.…”
Section: Topical Treatment For Erythematotelangiectatic Rosaceamentioning
confidence: 99%